2015
DOI: 10.1371/journal.pone.0125774
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Protein from Ganoderma microsporum Induces Pro-Death Autophagy through Akt-mTOR-p70S6K Pathway Inhibition in Multidrug Resistant Lung Cancer Cells

Abstract: Chemoresistance in cancer therapy is an unfavorable prognostic factor in non-small cell lung cancer (NSCLC). Elevation of intracellular calcium level in multidrug resistant (MDR) sublines leads to sensitization of MDR sublines to cell death. We demonstrated that a fungal protein from Ganoderma microsporum, GMI, elevates the intracellular calcium level and reduces the growth of MDR subline via autophagy and apoptosis, regardless of p-glycoprotein (P-gp) overexpression, in mice xenograft tumors. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…The present study identified that thapsigargin inhibits p-Akt and p-mTOR protein expression in prostate cancer cells. Chiu et al (22) demonstrated that thapsigargin induces pro-death autophagy through Akt-mTOR-Ribosomal protein S6 kinase β-1 pathway inhibition in multidrug-resistant lung cancer cells. These data suggest the role of thapsigargin-mediated inhibition of the Akt-mTOR pathway in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified that thapsigargin inhibits p-Akt and p-mTOR protein expression in prostate cancer cells. Chiu et al (22) demonstrated that thapsigargin induces pro-death autophagy through Akt-mTOR-Ribosomal protein S6 kinase β-1 pathway inhibition in multidrug-resistant lung cancer cells. These data suggest the role of thapsigargin-mediated inhibition of the Akt-mTOR pathway in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a lot of Chinese medicine monomers and compounds have been confirmed to show advantages in prolonging the survival period and reversing lung cancer drug resistance [3-5]. Shufeng Jiedu Capsule (SFJDC) was used in experiment and found that it reverses chemoresistance of H69AR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that rFIP-gts inhibited A549 cell proliferation by inducing premature senescence and G1 phase arrest [26]; rFIP-gmi induced A549 cell death by activating autophagy through the Akt-mTOR-p70S6K pathway but did not induce apoptotic cell death [27,28]; rLZ-8 mediated the G1 arrest of A549 proliferation via the ribosomal protein S7-MDM2-p53 pathway [29]; FIP-fve inhibits A549 migration via RacGAP1 and suppresses the proliferation of A549 cells via the p53 activation pathway [8]. All these studies indicate that FIPs from Ganoderma spp.…”
Section: Discussionmentioning
confidence: 99%